Factors associated with health-related quality of life among employed individuals with chronic obstructive pulmonary disease: A correlational study in China - Peihua Zhang; Niphawan Samartkit; Khemaradee Masingboon (Belitung Nursing Journal, 2023)
Background: The rising prevalence of chronic obstructive pulmonary disease (COPD) in China has led to a decline in the health-related quality of life (HRQOL) of employed individuals with the condition. Consequently, healthcare providers play a crucial role in identifying the factors associated with HRQOL in this population. Objectives: This study aimed to describe the HRQOL of employed individuals with COPD and determine the relationships between symptom burden, functional performance, social support, and HRQOL. Methods: A cross-sectional correlational research design was employed for this study. A total of 130 employed individuals with COPD who visited the respiratory outpatient department at the Second Affiliated Hospital of Wenzhou Medical University were selected through simple random sampling. Data were collected between August and September 2021 using a demographic questionnaire and four scales. Descriptive statistics and Pearson correlation were used for data analysis. Results: The study findings revealed that the mean HRQOL score among the participants was in the moderate range (M = 69.46, SD = 16.82). The correlation analysis revealed a significant negative association between symptom burden and HRQOL (r = -0.80, p <0.001). On the other hand, a positive relationship was observed between functional performance and HRQOL (r = 0.56, p <0.001), while social support did not show a significant relationship with HRQOL (r = 0.04, p >0.05). Conclusion: These findings serve as a foundation for healthcare service providers and policymakers in developing targeted nursing interventions and comprehensive management approaches for employed individuals with COPD. By addressing the symptom burden and promoting functional performance, nurses can strive to enhance the HRQOL of this population. Moreover, strategies to improve social support networks and facilitate access to emotional and practical assistance may further contribute to improving the overall well-being and satisfaction among employed individuals with COPD.